HYPERTONIC EXTENDERS IN THE CRYOPRESERVATION OF OVINE SEMEN - Guerrero V., Hernán (2009)
The cryoprotectant effect of two hypertonic extenders (trehalose and lactose) on the post-thawing characteristics of ram semen (n=4) was evaluated. The extender composition included Tris 27.1 g/l, Citric acid 14.0 g/l, Fructose 10.0 g/l, Glycine 10.0 g/l, egg yolk 10.0% (v/v) and Glycerol 6.5% (v/v). Semen was collected in an artificial vagina. Seminal characteristics were: volume: 1.1 ± 0.1 ml, sperm concentration: 3.50 ± 0.1 x 109/ml, individual motility: 87.0 ± 2.4%, wave motility (scale 0-5): 4.4 ± 0.2, live sperms: 90.2 ± 3.8%, and abnormal sperms: 1.8 ± 0.7%. Semen was frozen in 0.5 ml straws and stored in liquid nitrogen. Straws were thawed after 3 months. Results of post-thawing evaluation were: individual motility: 40.3 ± 5.9 and 30.0 ± 5.0%, and live sperms: 34.4 ± 6.6 and 24.3 ± 5.0% for the Trehalose and Lactose extenders respectively. Results showed a better ram semen cryopreservation when the Trehalose extender was used.